Freezing and Recovery Time of Red Flour Beetles - Huang, Joey; Marshall, Jeremy L. (My University, 2017)
Body size plays a critical role in animal survival. In fact, Bergmann's Rule states that larger animals should be more successful in colder environments (McNab 1971), although this may not be the case for ectotherms like insects (see Mousseau 1997). The underlying mechanism for this relationship is that larger animals have lower surface to volume ratios, thus making freezing more difficult (Schmidt- Nielsen 1984). So we tested the hypothesis on Red Flour Beetles to see if it holds for very small organisms. We found that hypothesis is supported by the experiment.